From propaganda to peace - Weiss, George (Technical Centre for Agricultural and Rural Cooperation, 2008)
Radio was used to incite hatred in the build up to the genocide in Rwanda. But today the medium promotes messages of reconciliation and peace to those still traumatized by the violence.